Pendampingan Terhadap Korban Kekerasan Seksual Di Yayasan Samahita Bersama Kita Bandung - Nadira Kowara; Muhammad Fedryansyah (Jurnal Ilmiah Rehabilitasi Sosial (Rehsos), 2024)
The research entitled Assistance for Victims of Sexual Violence at the Samahita Bersama Kita Foundation Bandung is research that will fully explain and describe the psychosocial assistance provided by the Samahita Bersama Kita Foundation Bandung in dealing with victims of sexual violence so that they can return to their social functions and help victims of sexual violence in their lives. fulfill their rights, as well as the development of assistance provided by the Samahita Foundation from time to time. The method used in this research is a qualitative method with a descriptive approach, using documentation studies and literature studies. The results of this research found that psychosocial assistance acts as a friend to tell stories to victims, so that victims have a safe and comfortable space in telling stories about cases that occurred and help victims restore their social functioning. Keyword: Mentoring, Samahita Bersama Kita Bandung Foundation, Sexual Violence